Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1029/2004gl020093
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range transport of Siberian biomass burning emissions and impact on surface ozone in western North America

Abstract: [1] During the summer of 2003, biomass fires burned a large area of Siberia, the largest in at least 10 years. We used the NRL Aerosol Analysis and Prediction System (NAAPS) model to forecast the transport of the smoke from these fires. Transport of these airmasses to North America was confirmed by aircraft and surface observations. The fires resulted in enhancements in summer background CO and O 3 of 23-37 and 5 -9 ppbv, respectively, at 10 sites in Alaska, Canada and the Pacific Northwest. From the area burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(261 citation statements)
references
References 22 publications
(24 reference statements)
11
248
1
1
Order By: Relevance
“…Therefore, it is difficult to utilize these monitors to identify dust events because the monitoring sites are either deployed far away from dust active regions (most likely collocated with dense population) or contaminated by anthropogenic sources. Even at rural or background sites, other natural sources, such as wildfires and vegetation detritus, and long-range transported dust can contribute to monitor readings (e.g., Edgerton et al, 2009;Jaffe et al, 2004). Consequently, it is difficult to directly utilize the measurement data from such monitoring networks to detect dust from local sources or to assess dust model performance.…”
Section: Q Tong Et Al: Long-term Dust Climatology In the Western Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is difficult to utilize these monitors to identify dust events because the monitoring sites are either deployed far away from dust active regions (most likely collocated with dense population) or contaminated by anthropogenic sources. Even at rural or background sites, other natural sources, such as wildfires and vegetation detritus, and long-range transported dust can contribute to monitor readings (e.g., Edgerton et al, 2009;Jaffe et al, 2004). Consequently, it is difficult to directly utilize the measurement data from such monitoring networks to detect dust from local sources or to assess dust model performance.…”
Section: Q Tong Et Al: Long-term Dust Climatology In the Western Usmentioning
confidence: 99%
“…High PM concentrations, however, do not warrant a local dust event. For instance, long-range transported Asian and African dust has been previously reported to cause air quality degradation in both the western and the eastern United States (Prospero, 1999;Jaffe et al, 2004;Fairlie, et al, 2007). To ensure the source of dust aerosols is local, we exclude the high PM data that is also associated with high PM 2.5 /PM 10 ratio.…”
Section: Approach To Identify Local Dust Recordsmentioning
confidence: 99%
“…Transport of pollution across the Pacific is well documented in the literature (e.g. Jaffe et al, 2004;Goldstein et al, 2004;Parrish et al, 2004) and has been the objective of various field campaigns. Bey et al (2001) examined aircraft data from the NASA Pacific Explatoratory Mission (PEM)-West B mission in February-March 1994 and found that frontal lifting of pollution over central and eastern China ahead of eastward moving cold fronts, followed by westerly transport in the lower free troposphere was the principal process for export of anthropogenic and biomass burning pollution from Asia.…”
Section: Introductionmentioning
confidence: 93%
“…Jaffe et al (2004) reported that the 2003 Russian forest burned area was 18.9 × 10 4 km 2 , which was more than twice the annual average for Russian fires between 1996 and 2003. Recent warming in boreal forest results in a tendency of drying which creates a positive feed back for the wildfire and global warming Murphy et al 2000).…”
Section: Forest Fire In May 2003mentioning
confidence: 99%
“…When a wildfire breaks out, the boreal forest becomes a large source of carbon dioxide. Therefore, the total area of the fire, the frequency, and the total amount of burned biomass are the great concern for the study of global warming Murphy et al 2000;Jaffe et al 2004).…”
Section: Introductionmentioning
confidence: 99%